2020
DOI: 10.3390/antiox9070633
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the MAPK/ERK and PI3K/AKT Signaling Pathways Affects NRF2, Trx and GSH Antioxidant Systems in Leukemia Cells

Abstract: The mitogen-activated protein kinase (MAPK)/extracellular signal kinase (ERK) and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signal transduction pathways have been implicated in the pathogenesis of leukemia. The aim of this study was to investigate the effect of the combination of ERK1/2 inhibitor AZD0364 and PI3K inhibitor ZSTK474 on acute lymphoblastic leukemia (ALL) REH, MOLT-4, acute myeloid leukemia (AML) MOLM-14, and chronic myeloid leukemia (CML) K562 cell lines. To evaluate the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…Comparatively, a recent study reported several plant‐based bioactive molecules such as caffeic acid and chrysophanol that exert their anticancer effects through inhibition of cell proliferation. [ 14,15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, a recent study reported several plant‐based bioactive molecules such as caffeic acid and chrysophanol that exert their anticancer effects through inhibition of cell proliferation. [ 14,15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, a recent study reported several plant-based bioactive molecules such as caffeic acid and chrysophanol that exert their anticancer effects through inhibition of cell proliferation. [14,15] It is reported that most of the cytotoxic agents stimulate apoptosis. ROS, which are largely yielded by the mitochondria, under pathological condition, may be excessively produced.…”
Section: Discussionmentioning
confidence: 99%
“…PTPs could dephosphorylate insulin receptor substrate protein 1 (IRS-1) in response to insulin-induced ROS and activate PI3K/AKT pathway subsequently, which plays a significant role in chemotherapy resistance [ 56 ]. Activation of the PI3K/AKT signaling pathway has been shown to be essential in modulating glutathione metabolism [ 57 ]. Besides, the activation of AKT is crucial in the regulation of GSH synthesis [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the PI3K/AKT signaling pathway has been shown to be essential in modulating glutathione metabolism [ 57 ]. Besides, the activation of AKT is crucial in the regulation of GSH synthesis [ 57 , 58 , 59 ]. Kim et al revealed that the AKT/p70S6K pathway was capable of manipulating the GSH biosynthesis activated by insulin [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Notch also downregulates the expression of protein kinase C θ (PKC-θ) through the runt-related transcription factor (RUNX) pathway, thereby inhibiting intracellular ROS accumulation and facilitating the maintenance of LIC activity [ 100 ]. In addition, numerous studies have shown that various antioxidant proteins, such as nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1), also have important regulatory roles in the antioxidant responses of ALL cells [ 111 , 112 ].…”
Section: Redox Regulation In Leukemiamentioning
confidence: 99%